Recurrent painful ophthalmoplegic neuropathy: A report on the patient from the Romani population and 82-year-old patient - Miletić-Drakulić Svetlana; Aleksić Dejan Zoran (Vojnosanitetski Pregled)
Introduction. The current diagnostic criteria for recurrent painful ophthalmoplegic neuropathy (RPON) are at least two attacks of unilateral headache, associated with ipsilateral paresis of one, two or all three cranial nerves (III, IV or VI). There is no case report about RPON in the Romany population. The oldest patient with RPON, published in the literature, was 74 years old. Case report. The first patient was a 31-year-old man from the Romani population who was treated during three episodes of RPON, with III nerve palsy during one episode and with alternating VI nerve palsy during two episodes. All examination were normal except serum lipid levels and Cytomegalovirus immunoglobulin G (CMV IgG), Toxoplasma gondii IgG, Epstein–Barr virus (EVB) IgG and Varicella zoster IgG which were elevated. The second patient was a 82-year-old male patient with two RPON episodes with alternating VI nerve palsy. All examinations were normal, except Herpes simplex type 1 virus IgG, CMV IgG, Toxoplasma gondii IgG, EBV IgG and Varicella zoster IgG which were elevated, and his brain magnetic resonance imaging (MRI) showed lacunar ischemic lesions. Both patients were started on corticosteroid. Recovery was completed after all five episodes of RPON. Conclusion. There are no data on the frequency of RPON among the Romani population. The presentation of RPON in the oldest age is rare. RPON should be considered as a diagnostic option in these minorities. New case reports or systematic review articles about RPON are necessary to create a new insight into the nature of the disease.